"Every Picture Tells a Story"; Picturing Judicial Biography. (12th March 2014) - Moran, Leslie J
Abstract: In this article Leslie J. Moran turns to objects that are often marginal to legal biography and neglected by those engaging in legal biographical projects; pictures. Drawing upon his previous and current work on judicial portraits the article outlines three biographical dimensions of these legal images. The first explores the legal biography potential of what lies within the frame of a judicial portrait. The second focuses upon the biographical dimensions of the process of portrait making. The third draws upon the now well established insight that the meaning of the object, the judicial portrait, is not generated exclusively by, or confined to, what is to be found within the frame of the picture. This provides an opportunity to consider the role of pictures as a method for use by those engaging in legal biographical projects.